Incidence and predictive factors of lower respiratory tract infections among the very elderly in the general population. The Leiden 85-plus Study. Issue 9 (3rd April 2008) - Sliedrecht, A; den Elzen, W P J; Verheij, T J M; Westendorp, R G J; Gussekloo, J
Abstract : Objectives: To target preventive strategies in old age, which of the very elderly are predisposed to developing lower respiratory tract infections was investigated. Design: Prospective observational follow-up study. Setting: General population. Participants: Unselected cohort of 587 participants aged 85 years in Leiden, The Netherlands. Measurements: As reported in the literature, predictive factors were selected and assessed at baseline. During a 5 year follow-up period, information on the development of lower respiratory tract infections was obtained from general practitioners or nursing home physicians. Associations between predictive factors were analysed with Cox regression, and population attributable risks were calculated. Results: The incidence of lower respiratory tract infections among persons aged 85–90 years was 94 (95% CI 80–108) per 1000 person years. After multivariate analysis, history of chronic obstructive pulmonary disease (COPD), smoking, oral glucocorticosteroid use, severe cognitive impairment, history of stroke and declined functional status remained independently associated with the occurrence of lower respiratory tract infections. Smoking was the greatest contributor with a population attributable risk of 32%. Conclusion: In the very old, smoking, COPD, stroke and declined functional status were associated with the occurrence of lower respiratory tract infections and provide a means of targeting patients at risk of severe health complications.